Ambiguity Aversion and the Term Structure of Interest Rates - Gagliardini, Patrick; Porchia, Paolo; Trojani, Fabio (Review of Financial Studies, 2009)
[This paper studies the term structure implications of a simple structural model in which the representative agent displays ambiguity aversion, modeled by Multiple Priors Recursive Utility. Bond excess returns reflect a premium for ambiguity, which is observationally distinct from the risk premium of affine yield curve models. The ambiguity premium can be large even in the simplest log-utility setting and is also nonzero for stochastic factors that have a zero risk premium. A calibrated low-dimensional two-factor model with ambiguity is able to reproduce the deviations from the expectations hypothesis documented in the literature, without modifying in a substantial way the nonlinear mean-reversion dynamics of the short interest rate. Moreover, the model does not imply any apparent trade-off between fitting the first and second moments of the yield curve.]